EVALUASI FLUID ABOVE PUMP UNTUK OPTIMASI ELECTRICAL SUBMERSIBLE PUMP PADA LAPANGAN SLN - Kurniadi, Ahmad Dzikri; Rahmawan, Sigit; Widiyatni, Harin (Petro : Jurnal Ilmiah Teknik Perminyakan, 2025)
The SLN field is a field that has several fields and produces fluids using artificial lift, specifically electrical submersible pumps (ESP). The objective of this research is to obtain the latest recommended value for fluid above the pump (FAP) by evaluating the FAP in each field within the SLN field. This will help determine the minimum fluid above the pump as a reference for future operations in the SLN field. In this study, the method used to calculate the fluid above the pump involves interpolating the FAP data with casing pressure, gas production, and gas-oil ratio (GOR) data. This is done to obtain the best regression graph and determine the minimum FAP value. Based on the research conducted on the evaluation of fluid above the pump in the Dik 01 and Dik 02 fields, the results for the Dik 01 field indicate that when the FAP is low, the gas production rate (Qg) and GOR are also low, indicating the absence of free gas. Conversely, when the FAP is high, there is an indication of free gas. The minimum FAP values obtained for the Dik 01 field are 1918 ft for Qg (Mscf/d) and 1967.44 ft for GOR (scf/stb). The results for the Dik 02 field show that a high FAP value corresponds to a low Qg and GOR, indicating the absence of gas. Conversely, a low FAP value corresponds to a high Qg and GOR, indicating the presence of free gas. The minimum FAP values obtained for the Dik 02 field are 3895 ft for Qg (Mscf/d) and 3776.32 ft for GOR (scf/stb).